Złożoność układów dynamicznych - Falniowski, Fryderyk (Complexity of dynamic systems, 2007)
In the context of dynamic systems, Grassberger has suggested that a slow approach of the entropy to its extensive asymptotic limit is a sign of complexity. He has introduced some measures of complexity called Effective Measure Complexity (or just Grassberger’s Complexity). Crutchfield and Packard have developed this idea on the field of information theory. This article transports their ideas into the field of measure theory and gives some interesting results for invariant measures on the space of infinite strings. There is also a proposition of using it in economics.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1189, s. 176-182